GENE ACTION STUDIES IN BELL PEPPER ( CTION STUDIES IN BELL PEPPER (Capsicum annuum L. var. grossum) FOR EARLINESS, YIELD AND YIELD CONTRIBUTING TRAITS UNDER PROTECTED CONDITIONS - JASMEEN KAUR; R S SPEHIA; NEHA VERMA (The Bioscan, 2019)
Selection of suitable breeding methodologies in bringing desirable improvement in crop plant require the complete knowledge about the nature of gene action involved in the inheritance of quantitative and qualitative traits. Gene action for earliness, fruit yield and yield attributing traits in bell pepper were studied through Line x Tester analysis by involving 16 crosses made by using 8 lines and 2 testers. A perusal of the data indicated that all the traits under study except for fruit shape index were higher in ó2 SCA as compared to ó2 GCA (average). Similarly dominant components of variance (ó2s) for most of traits were also higher than the additive components (ó2g). Further, variance ratio in F1 was found less than one for all the traits except fruit shape index (12.50), plant height (1.21) for which it was recorded higher than one. Hence, for majority of characters there was preponderance of non-additive gene action except for fruit shape index and plant height (cm) which reaffirms the importance of hybrids in bell pepper.